Macrothrombosis and stroke in patients with mild Covid‐19 infection. (25th June 2020) - Fara, Michael G.; Stein, Laura K.; Skliut, Maryna; Morgello, Susan; Fifi, Johanna T.; Dhamoon, Mandip S.
Abstract: Coronavirus disease 2019 (COVID‐19) is a pandemic disease currently affecting millions of people worldwide. Its neurological implications are poorly understood, and further study is urgently required. A hypercoagulable state has been reported in patients with severe COVID‐19, but nothing is known about coagulopathy in patients with milder disease. We describe cases of patients in New York City presenting with stroke secondary to large vessel thrombosis without occlusion, incidentally found to have COVID‐19 with only mild respiratory symptoms. This is in contrast to the venous thrombosis and microangiopathy that has been reported in patients with severe COVID‐19. Our cases suggest that even in the absence of severe disease, patients with COVID‐19 may be at increased risk of thrombus formation leading to stroke, perhaps resulting from viral involvement of the endothelium. Further systematic study is needed because this may have implications for primary and secondary stroke prevention in patients with COVID‐19.